Dynamic co-movements and diversification benefits: The case of the Greater China region, the UK and the US equity markets - Guidi, Francesco; Savva, Christos S.; Ugur, Mehmet (My University, 2016)
This paper investigates the level of long-run co-movements and short-run dynamics among the Greater China region (Hong Kong SAR, Mainland China and Taiwan), the UK and the US stock markets. Although stock-price-index (SPI) co-movements are established in the long-run, the dynamic analysis based on a fixed rolling window of 160 weeks points out only intermittent episodes of long-run co-movements. Using an asymmetric dynamic covariance approach, we find positive but low and insignificant conditional correlations between stock market returns. These findings indicate scope for diversification benefits, the extent of which is estimated on the basis of different portfolio choices. Our portfolio analysis indicates that both UK and US investors would have secured higher levels of mean returns on the diversified portfolio. Furthermore, pairwise tests of equality show that the differences in the Sharpe ratios are statistically significant only in the case of UK investors.
Keywords: Cointegration; Conditional correlation; Diversification; Rolling windows